Preferences for redistribution in Europe - Javier Olivera (IZA Journal of European Labor Studies, 2015)
This paper uses pseudo panel techniques and a fixed effects estimator to analyse the determinants of preferences for redistribution in 34 European countries over the period 2002-2012. The data is drawn from the six available waves of the European Social Survey. The main result is that changes in income inequality positively affect changes in preferences for redistribution over time. Though this result is predicted by standard political economy models, it has found little previous empirical support. This study shows that, at least in Europe, growing income inequality leads to more individual support for redistribution. The empirical results hold after performing a variety of robustness checks regarding the construction of pseudo panels, the use of lags and different measures of income inequality.
Keywords: D31; D63; D72; H20; 330; Redistribution; Income Inequality; Preferences for redistribution; Pseudo panels